Effect of Stress Management Program on Stress Level and Stress Management Ability of Nursing Students - Mokekhaow, Kanyawee; Sukrapat, Worapanit; Promla, Walainaree (Journal of The Royal Thai Army Nurses, 2021)
Stress is a learning barrier for nursing students. Finding stress management methods that are consistent with the problem is essential. The study was a quasi-experimental research. The purpose was compared stress and stress management ability of nursing students between before and after of the experiment group, treatment group and control group. The sample were 102 nursing students which moderate stress or more, match paired of stress score and stress management ability and simple random sampling were 51 people per group. The instruments were stress test, stress management ability questionnaire and stress management program. The reliability of questionnaires at 0.90 and 0.87, respectively. The data was analyzed by using means, standard deviation, and t-test. The results found that after the experiment, the treatment group had a significantly lower stress than before and significantly lower stress than the control group at the .01 level, the treatment group had a significantly more stress management ability than before and significantly more stress management ability than the control group at the .01 level. The suggest that nursing faculty administrators should consider implementing this stress management program to help nursing students with stress and should be maintained continuously to reduce the stress of students to severe mental health problems in the future.